New Trends in Geotechnical Engineering Resilience Development Inspired from an International Academic Conference - BAO Cheng-gang, LU Yi-wei, ZHAO Xu-dong (长江科学院院报)
In September 2023, the 12th International Conference on Geosynthetics (12th ICG) was held in Rome under the theme “Leading the Way to a Resilient Planet”. By reviewing and synthesizing three invited lectures,four keynote lectures, and major papers from the conference, we found that “resilience” and “sustainability” would be important future directions and they reflect the fundamental demands in the entire geotechnical engineering field. We put forward some future directions, particularly in the following areas, which were expected to become important research topics: (1) Life-cycle design will become the guiding approach for engineering design. This entails not only considering the construction phase and initial costs but also addressing the full operational lifespan and post-operational conditions and expenditures; (2) Reliability-based design methods and risk analysis, grounded in probability theory, will emerge as one of the principal methodologies for engineering design; (3) Prototype monitoring techniques will become indispensable tools for diagnosing engineering behavior and will serve as the foundation of life-cycle design. Various testing and monitoring technologies are expected to advance further; (4) More resilient and durable materials (such as geosynthetics) will continue to be developed and widely applied; (5) New and more resilient structural forms will emerge, and research into their working mechanisms will enter a new phase with enhanced simulation capabilities; (6) The intrinsic characteristics of rock masses as continuous media with structural planes and soils as particulate media will receive greater consideration in rock mechanics and soil mechanics research; (7) New numerical analysis methods(such as the Discontinuous Deformation Analysis, DDA) and artificial intelligence (AI) technologies will be increasingly integrated into geotechnical engineering, gradually transforming its design and analytical methodologies. In China, research has already begun in most of these areas, albeit to varying extents: some areas have made significant progress and are beginning to be applied in practice, such as (3), (4), and (7); Others have yielded some results but face divergent views and complicated paths forward, such as (2); Some areas have been recognized for their necessity and importance, but practical implementation is still lacking, such as (1); Others have yet to be initiated and require a renewed understanding of their significance, such as (5) and (6). This analysis inevitably reflects a limited perspective, and the author humbly invites comments and insights from readers.